2000
DOI: 10.1073/pnas.120178997
|View full text |Cite
|
Sign up to set email alerts
|

Neanderthal diet at Vindija and Neanderthal predation: The evidence from stable isotopes

Abstract: Archeological analysis of faunal remains and of lithic and bone tools has suggested that hunting of medium to large mammals was a major element of Neanderthal subsistence. Plant foods are almost invisible in the archeological record, and it is impossible to estimate accurately their dietary importance. However, stable isotope (δ 13 C and δ 15 N) analysis of mammal bone collagen provides a direct measure of diet and has been applied to two Neanderthals and various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
152
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(159 citation statements)
references
References 40 publications
(34 reference statements)
4
152
0
1
Order By: Relevance
“…Stable isotope analyses on Neandertal remains from Vindija have demonstrated that these Mousterian people obtained the vast majority of their dietary protein from meat and that this meat must have been obtained largely by hunting (Richards et al, 2000). This finding supports the indication that the much earlier Krapina Neandertals were efficient hunters of large game, including Merck's rhinoceros (Miracle, 1999).…”
Section: Discussionsupporting
confidence: 76%
“…Stable isotope analyses on Neandertal remains from Vindija have demonstrated that these Mousterian people obtained the vast majority of their dietary protein from meat and that this meat must have been obtained largely by hunting (Richards et al, 2000). This finding supports the indication that the much earlier Krapina Neandertals were efficient hunters of large game, including Merck's rhinoceros (Miracle, 1999).…”
Section: Discussionsupporting
confidence: 76%
“…As pointed out by Alexander Verpoorte (pers. comm., 2004) these hominins, and especially the later Neanderthals, had relatively large bodies that needed more energy than, the slender physique of modern humans (Sorensen and Leonard, 2001), and probably subsisted at a higher trophic level (and hence at a lower population density) than modern humans, as well illustrated for the Neanderthals by stable isotope studies of their bones (Richards et al, 2000). The virtual absence of dwelling structures (or the low investments in a built environment) (cf.…”
Section: Middle Pleistocene Europementioning
confidence: 99%
“…As shown by the evidence from Schö ningen and-to a lesser degree-Boxgrove, these hominins were capable hunters of large mammals and had become serious members of the carnivore guild. By Neanderthal times they had become top carnivores (Richards et al, 2000), possibly specialising in prime-age adult ungulates, a specialisation unknown in other carnivores and a good sign of niche separation (Stiner, 2002). In the Levant, late Neanderthal hunting activities may even have led to a decline of red deer and aurochs populations (Speth, 2004).…”
Section: Middle Pleistocene Europementioning
confidence: 99%
“…They place Neanderthals on the highest level of the food chain, and suggest that Neanderthals were top predators that obtained almost all of their dietary protein from animal resources, mainly medium and largesized herbivores from open-air areas (Lee- Thorp and Sponheimer, 2006). This interpretation is based on the comparison of their nitrogen isotopic signatures to that of contemporary animal bones, some of which come from the same sites and layers as the Neanderthal specimens (e.g., Richards et al, 2000Bocherens et al, 2005), and others that come from faunal accumulations that provide ecological niche information (e.g., Iacumin et al, 2000;Richards and Hedges, 2003). In all of these comparisons Neanderthals have much higher nitrogen values than those from herbivores such as the horse, reindeer (Rangifer tarandus), red deer, Spanish ibex, chamois, steppe bison (Bison priscus) or aurochs, and are similar to or a bit higher than those of predators such as the wolf, hyena and lion.…”
Section: Neanderthal Dietary Isotopic Evidencementioning
confidence: 99%